Economic Analysis of an Intensive, Zero-Water Exchange, Saltwater Shrimp Culture Demonstration Project in Nicaragua - Mayra López; Charles Adams; James C. Cato; Donald Sweat (EDIS)
This is EDIS document FE361, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published October 2002.